Does the agglomeration of high-tech industries improve the efficiency of China’s green economy? Analysis based on the marketization - Zhang, Na; Deng, Jinqian; Gu, Yue; Ahmad, Fayyaz (Frontiers in Environmental Science, 2023)
High-tech industries represent a country's advanced productivity, technological level and innovation ability, they carry the characteristics of green industries in terms of resource-saving and being environmentally friendly, and their agglomeration has a significant impact on the development of green economy. The marketization process, as an important macroenvironment for the development of high-tech industries, not only relates to the motivation of high-tech industry agglomeration but also affects the effectiveness of the agglomeration effect. It is unclear whether marketization plays a role in the relationship between high-tech industry agglomeration and green economy efficiency and whether this role has heterogeneity. Taking China's provincial panel data from 2001 to 2020, this paper constructs a panel threshold econometric model, and examines the threshold effect of the high-tech industry agglomeration impact on green economic efficiency under different marketization levels. (1) The high-tech industry agglomeration impact on green economic efficiency has a double-threshold effect due to the marketization level, with threshold values of 5.862 and 8.938, and the promotion effect is the highest in the second threshold range. (2) Under the influence of the government-market relationship, nonstate economic development, market intermediary organization development and legal environment, the impact of high-tech industry agglomeration on green economic efficiency has a single-threshold effect, with threshold values of 7.4950, 12.1960 and 11.6100. After crossing the threshold values, the impact changes from negative to positive. Factor market development has a double-threshold effect, with threshold values 10.3100 and 14.9210, and the impact changes from negative to positive and gradually increases. (3) Among the major industries, the pharmaceutical manufacturing industry (3.978 and 9.639) and the computer and office equipment manufacturing industry (3.359 and 9.639) have a double-threshold effect due to the marketization level, and the medical equipment and instrumentation manufacturing industry (9.494) has a single-threshold effect. This study is of great significance for China as it would help optimize the market environment and stimulate the green economy effect of high-tech industry agglomeration; moreover, it would provide a reference for other developing countries and transition economies.